Location choice of foreign direct investment by multinational corporations from emerging countries - Klimek, Artur (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
Traditional discussion regarding multinational corporations (MNC) generally assumes that only firms possessing certain distinguishing advantages can successfully operate abroad. This paper examines the issue of emerging multinational corporations (EMNC), which do not represent high-end technology or excellent products, although they have become important international players in their industries. Moreover, numerous EMNCs have been capable of acquiring their established competitors in foreign countries. The main goal of the paper was to investigate the motives of selecting particular locations of foreign direct investment by “new” multinationals from four largest emerging economies (Brazil, the Russian Federation, India and China). The method applied to investigate the research problem was a multiple linear regression. The econometric analysis was enhanced by some selected facts about the EMNCs
Argumenta Oeconomica, 2016, Nr 2 (37), s. 169-187
Keywords: international investment; multinational firms; mergers; acquisitions